2019
DOI: 10.1590/s1984-29612019015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Leishmania infantum DNA according to clinical stages of leishmaniasis in dog

Abstract: The aim of this study was to compare molecular tests used to diagnose Leishmania spp. in dogs with different stages of infection. Blood and conjunctival swab (CS) samples from dogs classified in four clinical stages were subjected to different PCR protocols (13A/13B, MC1/MC2, LITSR/L5.8S and LEISH-1/LEISH-2 primers). To the study, 22.3% (48/215) of dogs were classified as without clinical signs, 67.5% (145/215) stage I (mild disease), 7.0% (15/215) stage II (moderate disease) and 3.2% (7/215) stage III (severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
6
0
2
Order By: Relevance
“…However, our results show no statistical difference between ages. According to studies performed in Brazil and Tunisia, the highest prevalence was found in dogs with clinical stage II, i.e., moderate disease [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results show no statistical difference between ages. According to studies performed in Brazil and Tunisia, the highest prevalence was found in dogs with clinical stage II, i.e., moderate disease [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sterilized ultrapure water was the negative control. We performed PCR gel electrophoresis on 1.5% agarose gels and subjected PCR products to DNA sequencing as described by FERNANDES et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Many infected dogs remain without clinical signs; however, canine leishmaniasis (CanL) is a systemic disease characterized by nonspecific clinical signs (SOLANO-GALLEGO et al, 2011). L. infantum infection or DNA has been reported in several canine tissues, organs, and body fluids (TAFURI et al, 2004;SOLANO-GALLEGO et al, 2011;SILVA et al, 2016;FERNANDES et al, 2019), including those Silva et al present in the genital system (DINIZ et al, 2005;SILVA et al, 2008;AMARA et al, 2009;MANNA et al, 2012;BOECHAT et al, 2016;OLIVEIRA et al, 2016aOLIVEIRA et al, , 2016bMAGRO et al, 2017). In particular, infection of the canine reproductive tract has received substantial attention since venereal and vertical transmission were reported (PANGRAZIO et al, 2009;SILVA et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…utilizando o kDNA de Leishmania spp. (KOLTAS et al, 2016;FERNANDES et al, 2019), sendo sensível o suficiente para detectar kDNA de um único organismo (RODGERS et al, 1990). Já em cães, a PCR ITS-1 de suabe se mostrou uma técnica muito eficiente na detecção de Leishmania (STRAUSS- AYALI, et al, 2004).…”
Section: Alterações Clínicas E Diagnósticounclassified
“…É importante destacar que os gatos aqui estudados pertencem a abrigos de animais, onde a ocorrência de Lu. longipalpis, LVC e LF, já foi relatada em estudos anteriores (SPADA et al, 2014;ALVES-MARTIN et al, 2017;FERNANDES et al, 2019;LEONEL et al, 2020).…”
Section: Reação Intradérmica De Montenegrounclassified